Integrated Project-Based Learning (PjBL) Learning Tools STEM: Improving Students' Creative Thinking Skills - Sinaga, Angelina K.; Sitompul, Harun; Napitupulu, Efendi (RIRAI Publisher, 2024)
Integrated STEM-based PjBL learning devices are a learning context designed by teachers to motivate students to take part in learning activities so they can boost their creative thinking skills and discover new ideas. The goal of this study was to examine a learning tool that combines STEM with Project-Based Learning. It looks at whether this tool is suitable, effective, and easy to use in order to help improve creative thinking skills of fourth-grade students of Santo Paulus Martubung Elementary School - Medan. This type of research uses the Research and Development (R&D) development model. The results of the study revealed that the devices developed had significantly improved students' creative thinking skills. The increase in creative thinking skills can be seen from the average n-gain score of 0.49 (moderate increase category). The learning devices developed on the 'Care for the Environment' material are effective in significantly improving students' scientific literacy. The increase in scientific literacy can be seen from the average score of 0.64 (moderate increase category) and increased interest in science and technology, active participation in discovery activities (practice and projects), and responsible management of natural resources and the the area around us after using a project-based learning tool along with a specific method.